Impact De L’application De Deux Insecticides Agricoles (Furadan®, Decis®) Dans Les Casiers De Riziculture Irriguee, Sur Les Larves D’anopheles Gambiae, Vecteur Du Paludisme A Bouake, Au Centre De La Côte d’Ivoire - Boby Ouassa Anne-marie; Tia Emmanuel; Boka Ohoukou Marcel; Kadjo Kouamé Alphonse (European Scientific Journal, ESJ, 2016)
The impact of two agricultural insecticides on larvae of Anopheles gambiae, the malaria vector, has been studied in an experimental scope in Bouaké, Côte d'Ivoire. The Furadan® (carbofuran) and the Décis® (deltamethrin), pesticides commonly used against pests of rice, were applied in irrigated rice bins 15 days after sowing or transplanting, using operational doses of 28 kg / ha and 1l / ha recommended by the manufacturer. Each rice paddy was replicated 3 times and all these replicas were arranged in 3 randomized complete block. Larvae were sampled according to Dipping method before and after insecticide treatments. Water lockers was also charged for persistence tests. Determining the density live larvae showed total disappearance thereof in the 3rd day (3 days after treatment) before reappearing on the 5th day. Insecticides persistence tests have given a larval mortality at 1 day 97.8% to 100% for the Furadan® and 45.92% to 86.45% for the Décis®. This mortality was less than 50% for both insecticides on the 5th day. In Conclusion insecticides used (Décis®, Furadan®), induce a high mortality of larvae of Anopheles gambiae. However, if these insecticides have a low persistence (<1 week) that their activity period does not cover the proliferation period of this species in irrigated rice (2-4 weeks).